Whole-genome sequencing of multiple isolates of Puccinia triticina reveals asexual lineages evolving by recurrent mutations. Issue 9 (8th July 2021) - Fellers, John P; Sakthikumar, Sharadha; He, Fei; McRell, Katie; Bakkeren, Guus; Cuomo, Christina A; Kolmer, James A
Abstract: The wheat leaf rust fungus, Puccinia triticina Erikss., is a worldwide pathogen of tetraploid durum and hexaploid wheat. Many races of P. triticina differ for virulence to specific leaf rust resistance genes and are found in most wheat-growing regions of the world. Wheat cultivars with effective leaf rust resistance exert selection pressure on P. triticina populations for virulent race types. The objectives of this study were to examine whole-genome sequence data of 121 P. triticina isolates and to gain insight into race evolution. The collection included isolates comprising of many different race phenotypes collected worldwide from common and durum wheat. One isolate from wild wheat relative Aegilops speltoides and two from Ae. cylindrica were also included for comparison. Based on 121, 907 informative variants identified relative to the reference Race 1-1 genome, isolates were clustered into 11 major lineages with 100% bootstrap support. The isolates were also grouped based on variation in 1311 predicted secreted protein genes. In gene-coding regions, all groups had high ratios of nonsynonymous to synonymous mutations and nonsense to readthrough mutations. Grouping of isolates based on two main variation principle components for either genome-wide variation or variation just within the secreted protein genes, indicated similar groupings. Variants were distributed across the entire genome, not just within the secreted protein genes. Our results suggest that recurrent mutation and selection play a major role in differentiation within the clonal lineages.